(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article is devoted to study a language as a part of general knowledge. In the study of language, grammar occupics a central position. But there is also a practical reason to emphasize the study of grammar it is easy to learn to use dictionaries by yourself to find the pronunciation, spelling, or meaning of words, but it is to consult grammar books without a considerable knowledge of grammar.